How knowledge became limited because of the scientific method: the story of non sense - Pawan Ahmad, Isham (Research Management Centre, International Islamic University Malaysia, 2017)
Faruqi’s project of Islamization mainly focused on social sciences because the social science dealt with man and society. It had somewhat neglected scrutinizing modern natural science arguing that natural science dealt with nature and therefore neutral and objective (Kalin, 2002). However, it is the natural science methodology that dominates and shapes social science methodology and questions. More importantly, the scientific methodology has reduced all matters to physical things and all knowledge reduced to physical knowledge. Any and all non-physical knowledge initially was beyond the scientific methodology to prove right or wrong because the limitations of the physical methodology were held in abeyance and were not judged upon and considered scientifically meaningless. Mach’s dictum that “where neither confirmation nor refutation is possible, science is not concerned (Mach, MACCORMACK, & Menger, 1960). Logical positivism adopting Wittgenstein’s verification criteria that seeks to legitimize all discourse by placing it on a basis shared with empirical evidence only statements verifiable either by direct observation or logical deductions would be cognitively meaningful changed everything. Now, any and all non-physical knowledge becomes non sense statements. These statements become absurd statements, unable to be proven by the only criteria acceptable, the scientific physical methodology and thus become no longer worthy of study. We must engage with science, in fact celebrate science but at the same time, we must also constraint science and guide it with our ethico-religious world view that will make science a true blessing for all mankind. In order to do this, we must purify religion from error and superstition, re-appropriate science as a study of sunnah Allah and institutionalize critical and rational thinking within society.